Analisis Hidrograf Satuan Terukur Sub DAS Way Besai - Astriyana, Mega; Kusumaastuti, Dyah Indriana; Purwadi, Ofik Taufiq (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Way Besai River is the largest river in west lampung district. High sedimentation in this riveraffects the performance of Hydroelectic Power Plant (HEPP) owned by PLN which is located inWay Besai River. In order to know the condition of Way Besay’s catchment area, a research isconducted on each of Way Besai’s sub catchment area. One of the sub catchment area is located inTalang Bandung Village, Pekon Sindang Pagar, Kel Tugu Sari Kec Sumber Jaya West LampungDistrict named Talang Bandung Catchment and Air Anak Catchment. In order to make the surveyof Catchments condition easier, the research uses measured unit hydograph analysis method. Thepurpose is to analyse the measured unit hydograph in order to get the value of Peak Discharge,Peak time, basic time, and analysing the flood hydrograph.In this researc the data needed are automatic rainfall data, automatic water level data, velocitydata, and the stream cross section. From these data will be used to make Rating Curve to turn thehydrograph of water level into flow hydrograph. The separation of the components of base flowand direct runoff using straight-line approach and calculate the efective rainfal to get the ordinateof unit hydrograph. From the average of unit hydrograph combined with periodic rainfall willobtain the periodic flood hydrograph.From the analysis result it is, obtained an average of hydrograph unit for each catchment area. On60 minutes period, the average of unit hydrograph of Air Anak Catchment and Talang BandungCatchment have average peak discharge average (Qp) of 0,340 m 3 /sec and 0,394 m 3 /sec, the timeof rise are 560 minutes and 660 minutes. The result shows that for return period of 25 years, flooddischarge for Air Anak is 16,832 m 3 /sec and for Talang Bandung is 20,179 m 3 /sec.Keywords: Measured Unit Hydrograph Analysis, Sub Catchment Area of Way Besai.